Global Ibsen performing multiple modernities - Fischer-Lichte, Erika; Gronau, Barbara; Weiler, Christel (New York Routledge, 2011)
'Global Ibsen' the different ways in which Ibsen's plays were & are performed in different cultures on five continents & examines the impact of such performances on the theatre, social life & politics of these cultures. It shows that performing Ibsen means performing multiple modernities.
Introduction / Erika Fischer-Lichte -- What happened to the women's liberation movement? A doll's house and Hedda Gabler on stage. Ibsen on the Platteland : the first professional production of A doll's house in Afrikaans goes on tour (1929) / Temple Hauptfleisch and Hilda van Lill -- Ibsen's A doll's house in America / Marvin Carlson -- A doll's House in the Antipodes / Jacqueline Martin --Canajun-eh? finding a house for Nora in Canada / Errol Durbach -- Women's issues and a new art of acting : A doll's house in Japan / Mitsuya Mori -- Against love : Nora and Hedda on the contemporary Scandinavian stage / Tiina Rosenberg -- Deborah Warner directs Hedda Gabler : mercurial pistols / Maria Shevtsova -- Performing Peer Gynt : negotiating cultural identity. Peer Gynt by the Pyramids in Giza / Nehad Selaiha -- Peer Gynt in Israel : a national hero returning from exile? / Freddie Rokem -- Antunes Filho's Peer Gynt : a remarkable production of Ibsen in Brazil / Thereza Menezes -- Patrice Chareau's Peer Gynt : a renewed reception of Ibsen's theater in France / Catherine Naugrette -- Werner Egk's Peer Gynt in Berlin 1938- opera and politics / Clemens Risi -- Modernization of society and the emergence of a new theatre. Ghosts and gods : Ibsen, tragic actors and modern tragedies in contemporary Greek theater practice / Platon Mavromoustakos -- An enemy of the people : the play that anticipates the future / Wang Ning -- An enemy of the people as a Trojan horse : Frank Castorf stages Ibsen in the German Democratic Republic 1988 / Barbara Gronau (Germany) -- Eleonora Duse and Gordon Craig's Lost Ibsen / Laura Caretti -- A brilliant failure : rosmersholm at the Moscow Art Theater (1908) and its first studio (1918) / Dmitry Trubotchkin.
Includes bibliographical references and index.
Keywords: Ibsen, Henrik -- 1828-1906 -- Stage history -- Foreign countries; Ibsen, Henrik -- 1828-1906 -- Dramatic production; Ibsen, Henrik -- 1828-1906 -- Criticism and interpretation; Modernism (Literature).; Feminism and literature